A PROFESSION RECOMMENDER SYSTEM BASED ON DEEPLEARNING AND MACHINE LEARNING APPROACHES - Iskalinov, Farukh (Journal of Emerging Technologies and Computing, 2024)
The issue of uncertain career path choice among modern schoolchildren has become increasingly prominent, resulting in a substantial decrease in the number of university students. This uncertainty has become a major concern as students and their parents are often unfamiliar with the wide range of available professions, particularly those that have emerged in the last decade. A modern solution is proposed in the form of a web application that uses Deep Learning, Machine Learning, and NLP to recommend suitable specialtiesbased on the competencies required for the profession. The system will analyze and extract implicit features through a supervised classification approach, providing a comprehensive solution for profession search in the Kazakhstan market.